Analysis of Genetic Structuralism in the Novel Alf Syams Musyriqah by Khaled Hosseini - Apriliyanti, Bunga; Abunawas, Kamaluddin; Ahmad, Muhsin; Kastang, Aprilia (International Journal of Religion Education and Law, 2025)
This research presents four problem formulation items, namely: First, what is the structure of the novel Alf Syams Musyriqah? Second, what are the social facts in Alf Syams Musyriqah's novel? Third, what is the collective subject in Alf Syams Musyriqah's novel? Fourth, what is Khaled Hosseini's world view in Alf Syams' novel Musyriqah? This type of research is library research. The approach used is a literary sociology approach using the theory of genetic structuralism as an analytical tool. The data collection method used in this research is literature study. The data analysis technique used in this research is the dialectical technique which is part of genetic structuralism. The results of this research show that: First, the structure of the novel Alf Syams Musyriqah by Khaled Hosseini raises three themes, namely the themes of patriarchy, domestic violence, and the impact of war and political conflict. The setting in Alf Syams Musyriqah's novel is divided into two, namely the setting of place and the setting of time. The settings in this novel include Herat, Kabul, Shahr-e-Nau Park, Murree, school, women's prison and hospital. The time setting in this novel includes the era of King Zahir Shah's monarchy, the Daoud Khan regime, the Soviet Union regime, the Mujahideen regime, the Taliban regime, the American invasion and the collapse of the Taliban regime. Second, the social facts in Alf Syams Musyriqah's novel are: Political Conflict and War in Afghanistan, the Afghan refugee crisis, patriarchal culture, which includes restrictions on women's freedom, early marriage and domestic violence. Alf Syams' novel Musyriqah is not only a work of fiction, but also a reflection of the socio-historical reality of Afghanistan. Hosseini raised various phenomena that occurred in his home country in his literary works, especially in the novel Alf Syams Musyriqah, which aims to raise global awareness about the situation in Afghanistan. Third, through lower class figures, namely Mariam and Laila, Hosseini represents the collective voice of the oppressed Afghan people, especially women who are victims of political conflict, domestic violence and social injustice. Fourth, Khaled Hosseini's world view in Alf Syams' novel Musyriqah is a feminist view. Hosseini spoke out about gender equality and the importance of women's empowerment in building a better future for Afghanistan. Through the characters Maryam and Laila, Hosseini voices his views through a depiction of how women are able to survive and fight oppression even though they are trapped in a restrictive patriarchal culture.The implication of the results of this research is that this research is expected to provide a deeper understanding of how Khaled Hosseini's empirical life influenced the formation of Alf Syams' novel Musyriqah, as well as how the novel responds to and reflects the socio-cultural conditions of Afghan society. Apart from that, it is hoped that the results of this research can be an inspiration and reference for other researchers who use genetic structuralism theory or use Alf Syams Musyriqah's novel as a research object.